Peripheral arterial disease and Virchow’s triad - Bennett, Philip C.; Silverman, Stanley H.; Gill, Paramjit S.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2009)
Peripheral arterial disease (PAD) is an important global health-care problem associated with considerable morbidity and mortality. This disease is an important manifestation of atherosclerosis and the pathophysiological processes involved in its development, progression and complications are atherothrombosis and thromboembolism. Over 150 years ago, Virchow described a triad of abnormalities (abnormal blood flow, abnormal vessel wall and abnormal blood constituents) associated with thrombus formation (thrombogenesis). An improvement in biochemical techniques has allowed quantification of various components of Virchow’s triad, and as a consequence, there has been increasing interest in the measurement of such biomarkers in understanding the development and progression of PAD, as well as its symptomatic complications. This review discusses quantifiable components of Virchow’s triad that have been associated with PAD and their clinical utility as risk factors for PAD.
Keywords: Arterial thrombosis; clinical studies; risk factors